Las Excepciones Previstas en el Código Orgánico General de Procesos para los Procedimientos Ejecutivos - Ojeda Coello, Julio Andrés (2019)
The changes integrated in the Administrative Procedure of the General Organic Code, intehrating a list of exclusive exceptions in the executive trial. The aim of this research is to determine the relevance of a specific Administrative Procedure to raise the exceptions that it does not exist. The research appoach is qualitative – descriptive explicity based on the analysis of articles 353 and 153 of the General Organic Code of Processes and Social doctrine. By way of conclusion, it is determined that there are different criteria between judges and lawyers and on personal judgement that there should be a specific procedure